Development of a carbon neutral process for producing renewable charcoal - Russell, Scott H. (2018)
This thesis investigates the process conditions, charcoal composition and biomass sources for process development of BBQ charcoal briquette production. This aim has been achieved by three areas of investigation: 1. Experimental pyrolysis at lab and pilot scale, with the aim of determining optimal process conditions and if addition of low cost catalyst material is beneficial to slow pyrolysis. 2. BBQ charcoal combustion and modelling of the fire temperature history to determine the pyrolysis conditions and allowable concentrations of non-charcoal additive important to the final charcoal briquette. 3. Techno-economic and carbon analysis (TEA) of the various options for by-product utilisations and determination of important process conditions. The novel findings from the experimental and modelling studies add to the literature on catalytic slow pyrolysis and lump char combustion, whilst applying these concepts to present optimal process flows and conditions for BBQ charcoal production. 1. The addition of low cost acidic and basic catalyst such as bentonite clay or dolomite to the slow pyrolysis of biomass can significantly increase the charcoal yield, and significantly improve the process economics. This also improves the quality of by-product liquid, high in low molecular weight phenolic compounds. 2. Lump charcoal combustion in a grate burner can be simulated by applying the analogy of a two first order chemical reactions in series model to the temperature profile of a simple combustion experiment. The model only requires proximate analysis of the charcoal briquette, and is valid up to briquette mixtures containing 30% inert or raw biomass additive. 3. Temperatures, around 450°C, are required. Lower temperature increases charcoal yield and therefore process economics and this is not too low to produce poor quality charcoal. 4. Processes either A) utilising the gas and liquid by-products in a combined heat and power engine or B) recovering the chemical stream as phenolic oils and using the gas stream to produce heat are the most economic and carbon efficient outcomes. 5. Addition of clay minerals are key to the economic success of both processes by increasing charcoal yield and producing better quality oil high in low molecular weight phenolic compounds.